STUDENTS ABILITY OF SMP TO SOLVE PROBLEMS MATHEMATICLLY CREATIVE THINKING - Nila Kesumawati (Jurnal Dosen Universitas PGRI Palembang)
AbstractThe purpose of this study is to determine the ability of SMP students to solve mathematically creative thinking problems. The research method is descriptive method. The participants of this research were 180 students in the Palembang. Methods of data collection using essay test. The result showed taht the ability of SMP students to solve mathematically creative thinking problems only 40,57 classified in low category.Keywords: the ability, the questions, the material fractions, mathematically creative thinking.